Vanilla production in the world and Mexico: Market value and technology - Alejandro Barragán-Ocaña; Paz Silva-Borjas; Erick Cecilio-Ayala (Social Sciences and Humanities Open)
Vanilla and vanillin are essential commodities for the food, pharmaceuticals, cosmetics, and tobacco industries. However, the global production of natural vanillin is insufficient to meet its demand and has been replaced by synthetic or biotechnological substitutes. Consequently, the opportunity to promote this sector is being missed, and the introduction of natural products with higher added value into the market is not encouraged. Therefore, this study sought, first, to conduct a study about the production and value of vanilla cultivation in Mexico and the world, and second, to examine the technology sectors that have developed around the production and processing of vanilla and vanillin. The methodological development includes: a) an export behavior study and a three-year forecast; b) a factor analysis to build a crop production index; c) the identification of conglomerates to define groups according to their behavior; and d) patent and network analyses to show the main technological sectors, countries, and applicants of technologies relevant to our object of study. Results show that vanilla production is dominated by countries such as Madagascar and Indonesia; although Mexico presents positive results in terms of yield, its participation is limited, in spite of having the appellation of origin for this crop. Data on Mexico indicate that technological development is being carried out by foreign companies and is oriented toward the industrial use of vanillin, disregarding agricultural development. The literature and results point to a lack of a public policy in México to promote this sector and insufficient scientific and technological development to achieve sustainable production. Training and market plans for the benefit of small producers should also be facilitated to boost their participation in the international arena.